Tissue sodium concentration and sodium T1 mapping of the human brain at 3 T using a Variable Flip Angle method - Coste, Arthur; Boumezbeur, Fawzi; Vignaud, Alexandre; Madelin, Guillaume; Reetz, Kathrin; Le Bihan, Denis; Rabrait-Lerman, Cécile; Romanzetti, Sandro (Magnetic resonance imaging, 2019)
The state-of-the-art method to quantify sodium concentrations in vivo consists in a fully relaxed 3D spin-density (SD) weighted acquisition. Nevertheless, most sodium MRI clinical studies use short-TR SD acquisitions to reduce acquisition durations. We present a clinically viable implementation of the Variable Flip Angle (VFA) method for robust and clinically viable quantification of total sodium concentration (TSC) and longitudinal relaxation rates in vivo in human brain at 3 T. Two non-Cartesian steady-state spoiled ultrashort echo time (UTE) scans, performed at optimized flip angles, repetition time and pulse length determined under specific absorption rate constraints, are used to simultaneously compute T1 and total sodium concentration (TSC) maps using the VFA method. Images are reconstructed using the non-uniform Fast Fourier Transform algorithm and TSC maps are corrected for possible inhomogeneity of coil transmission and reception profiles. Fractioned acquisitions are used to correct for potential patient motion. TSC quantifications obtained using the VFA method are validated at first in comparison with a fully-relaxed SD acquisition in a calibration phantom. The robustness of similar VFA acquisitions are compared to the short-TR SD approach in vivo on seven healthy volunteers. The VFA method resulted in consistent TSC and T1 estimates across our cohort of healthy subjects, with mean TSC of 38.1 ± 5.0 mmol/L and T1 of 39.2 ± 4.4 ms. These results are in agreement with previously reported values in literature TSC estimations and with the predictions of a 2-compartment model. However, the short-TR SD acquisition systematically underestimated the sodium concentration with a mean TSC of 31 ± 4.5 mmol/L. The VFA method can be applied successfully to image sodium at 3 T in about 20 min and provides robust and intrinsically T1-corrected TSC maps.